Pengaruh Pencahayaan Buatan Terhadap Persepsi dan Pengalaman Pengunjung di Taman Kota Sewaka Dharma - Wulandhari, Kadek Sri; Asmiwyati, I Gusti Agung Ayu Rai; Pradnyawathi, Ni Luh Made (Jurnal Arsitektur Lansekap; Vol.7, No.2, Oktober 2021DO - 10.24843/JAL.2021.v07.i02.p07, 2021)
The effect of artificial lighting on visitors' perceptions and experiences in Sewaka Dharma City Park. Lighting is one factor that is quite important in a garden because it can make the environment comfortable and safe, especially at night. Sewaka Dharma City Park is a green open space in Denpasar which is equipped with various lighting facilities with aesthetic values. This study aims to identify the type and placement of artificial lighting, determine the perceptions and experiences of visitors to artificial lighting from the aspect of human needs and provide recommendations for artificial lighting designs in Sewaka Dharma City Park. The data collection methods used were observation, questionnaires, interviews, and literature study with tabulated data analysis, Chi-square test and descriptive analysis. There are eleven types of existing lights located in the pathway area, lawn, CPG (Children Playground), and youth park. The Chi-Square test shows that artificial lighting affects visibility and visual comfort aspects, but does not affect the visitor's security experience, which can also be interpreted that artificial lighting in Sewaka Dharma City Park fulfills security aspects so as to minimize unsafe actions for visitors. This study recommends the types and placements of artificial lighting in areas that have a high influence in supporting human needs from the aspect of visibility and visual comfort, namely in the CPG area and youth park.